2020
DOI: 10.3389/fmed.2020.00071
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Modulates Macrophage Polarization and Mitigates Liver Inflammation and Fibrosis in a Murine Model of Nonalcoholic Steatohepatitis

Abstract: This study aimed to investigate the beneficial effects of myricetin in a diet-induced nonalcoholic steatohepatitis (NASH) model and the underlying mechanism. C57BL/6J mice were fed a standard chow or the choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD) for 8 weeks with the treatment of myricetin (100 mg/kg) or vehicle by daily gavage. Hepatic inflammation, steatosis, fibrosis, and hepatic stellate cells (HSC) activation were assessed. We also analyzed M1 and M2 macrophages and its related marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…In addition, Yao et al. ( 164 ) found that myricetin suppressed M1 and promoted M2 polarization by inhibiting the TREM-1-TLR2/4-MyD88 signaling pathway and the phosphorylation of STAT3, thus attenuating the NASH induced by choline-deficient, L-amino acid-defined, and high-fat diet. β-cryptoxanthin and astaxanthin, two carotenoids with anti-oxidant effects, could inhibit M1 macrophage polarization to improve insulin resistance and NASH induced by a high-cholesterol and high-fat diet in mice ( 165 , 166 ).…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
“…In addition, Yao et al. ( 164 ) found that myricetin suppressed M1 and promoted M2 polarization by inhibiting the TREM-1-TLR2/4-MyD88 signaling pathway and the phosphorylation of STAT3, thus attenuating the NASH induced by choline-deficient, L-amino acid-defined, and high-fat diet. β-cryptoxanthin and astaxanthin, two carotenoids with anti-oxidant effects, could inhibit M1 macrophage polarization to improve insulin resistance and NASH induced by a high-cholesterol and high-fat diet in mice ( 165 , 166 ).…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
“…Then, these inflammatory factors will induce the activation of HSCs [58]. When TREM1 is inhibited, the TREM1-TLR2/4-MyD88-mediated inflammatory signaling pathway is inhibited, and the polarization of M1-type macrophages are also reduced [101]. TREM2 expressed on KCs and HSCs dampen TLR4-induced inflammation, and the combined action of liver resident and infiltrating cells is also necessary to dampen inflammation [20].…”
Section: Roles Of Trem In Hepatic Fibrosismentioning
confidence: 99%
“…Wang et al demonstrated that trans-cinnamic acid has antiobesity effects in oleic acid- (OA-) induced HepG2 cells and high-fat diet- (HFD-) fed mice [ 92 ]; however, the role played by trans-cinnamic acid in HSCs remains unclear. Myricetin modulated the polarization of macrophages via the inhibition of TREM-1-TLR2/4-MyD88 signaling molecules in macrophages and attenuated liver inflammation and fibrosis in a choline-deficient, L-amino acid-defined, high-fat diet-induced nonalcoholic steatohepatitis model [ 93 ]. Quercetin caused decreased oxidative stress and inflammation and prevented liver fibrosis via the induction of HSC apoptosis [ 94 ].…”
Section: Discussionmentioning
confidence: 99%